Medical science and philosophy in the reflection of existentialist philosophers. - Carrasco de Paula, Ignacio; Pennacchini, Maddalena (Medicina e Morale, 2004)
For positivist philosophers, science is the only possible form of knowledge and its method is the only valid. Therefore, positivists don't admit the recourse to causes or principles that are not referable to scientific method. The enunciation of common principles of many sciences is philosophy's only concern. Philosophy has this task: to collect and coordinate results of single sciences in order to realize a unified and general knowledge. On the contrary, K. Jaspers and V. von WeizsÃ¤cker considers science and philosophy as two distinct ways that lead to knowledge. They put the two disciplines on two distinct levels, for the salvation of relationship between them. But this is a distinction of the subject matter and method that needs a conciliation, because the fundamental limit of the scientific knowledge is just in the nature of its method. Science, limited by its method that imposes it to keep to the objectivity hypothetically built, doesn't reach the truth of things, better its exactness. So sciences don't know the world but the order of world supposed by them. Against this position, Jaspers reacted asserting that scientists must learn to think, and this pedagogical objective must be pursued by philosophy.